2010
DOI: 10.1002/cne.22263
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factor receptor‐3 mRNA in the rat developing forebrain and retina

Abstract: Vascular endothelial growth factor receptor (VEGFR)-3, a receptor for VEGF-C and VEGF-D, is expressed in neural progenitor cells, but there has been no comprehensive study of its distribution in the developing brain. Here, the temporal and cell-specific expression of VEGFR-3 mRNA was studied in the developing rat forebrain and eye. Expression appeared along the ventricular and subventricular zones of the lateral and third ventricles showing ongoing neurogenesis as early as embryonic day 13 but was progressivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 80 publications
(88 reference statements)
2
16
0
Order By: Relevance
“…Thus, it is possible that VEGFR-3 is expressed in these unique neurogenic zones, which are thought to retain the capacity of generating new neurons and glia in the adult brain. This suggestion is supported by our previous findings (Choi et al, 2010) that VEGFR-3 is expressed in the subventricular zone of the lateral ventricle and the rostral migratory stream of the mature forebrain, where neural stem cells reside (Doetsch et al, 1999;Ihrie and Alvarez-Buylla, 2008;Mendoza-Torreblanca et al, 2008).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Thus, it is possible that VEGFR-3 is expressed in these unique neurogenic zones, which are thought to retain the capacity of generating new neurons and glia in the adult brain. This suggestion is supported by our previous findings (Choi et al, 2010) that VEGFR-3 is expressed in the subventricular zone of the lateral ventricle and the rostral migratory stream of the mature forebrain, where neural stem cells reside (Doetsch et al, 1999;Ihrie and Alvarez-Buylla, 2008;Mendoza-Torreblanca et al, 2008).…”
Section: Discussionsupporting
confidence: 69%
“…We showed that radial glia in embryonic forebrain, Mü ller glial cells and Bergmann glia expressed VEGFR-3 (Choi et al, 2010;Hou et al, 2011). Furthermore, VEGFR-3 is upregulated in SVZ astrocytes, type B cells in the SVZ of stroke-lesioned rats, which share some characteristics with radial glia-like cells (Shin et al, 2010a).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The VEGFR3 gene is highly transcribed in postnatal brain both in a subset of retinal neurons and in glial precursor cells [52], whereas VEGF-C and VEGF-D are variably produced by different neuronal and glial cells [22]. In addition, VEGF-C receptor VEGFR3 is expressed in neural progenitor cells in Xenopus laevis and mouse embryos [53].…”
Section: Vegf Function In Higher Eukaryotesmentioning
confidence: 99%
“…Vegf-c deletion in the mouse, as well as VEGF-C knockdown in Xenopus tadpoles, inhibited proliferation of neural progenitor cells in the forebrain, without defects of the brain vasculature, indicating that VEGF-C is a trophic factor for subsets of neural progenitor cells in the vertebrate embryonic brain (LeBras et al 2006). The high-affinity VEGF-C receptor VEGFR-3 is also expressed by embryonic and adult neural cells (Choi et al 2010;Calvo et al 2011). Using transgenic VEGFR-3 mice expressing a YFP reporter or conditional deletions of VEGFR-3 in neural cells, we have shown that, in the adult SVZ, VEGF-C/VEGFR-3 signaling acted in niche astrocytes and NSCs to stimulate neurogenesis (Calvo et al 2011).…”
Section: Vegf Signaling In Neuronal Progenitors During Development Anmentioning
confidence: 99%